ANURAN NATURAL HISTORY FROM SERRA DONA FRANCISCA, AN ATLANTIC FOREST REMNANT IN SOUTHERN BRAZIL (Boletín de la Sociedad Zoológica del Uruguay, 2022)
The Serra Dona Francisca is located in the subtropical region of the Atlantic Forest and part of its area is protected by a sustainable use conservation unit. In the present study, we performed an anuran inventory at different elevation, providing information on natural history of each species. Field work was carried out from October 2012 to January 2014. We sampled the anuran by active search and used three 50-meter pitfall lines composed of four 60L buckets with drift-fences at each elevation area. We registered 63 species belonging to 13 families: Brachycephalidae (4), Bufonidae (4), Centrolenidae (1), Craugastoridae (1), Cycloramphidae (2), Hemiphractidae (2), Hylidae (30), Hylodidae (2), Leptodactylidae (10), Microhylidae (2), Odontophrynidae (3), Phyllomedusidae (1), and Ranidae (1). We observed four new records for the northeastern region of Santa Catarina state: Bokermannohyla luctuosa, Scinax aromothyella, Odontophrynus americanus, and Leptodactylus plaumanni. We registered a higher number of species during the hot and wet months, with subsequent drop during the cold months. We found an increase of species richness at higher elevations. Considering our results that represent 50% of anuran richness of the Santa Catarina state, this is an important region for conservation of biodiversity of southern Atlantic Forest.
Keywords: Subtropical; anura; conservation; inventory